Human Capital Flight in Pakistan: Strategies for Coping Brain Drain Situation - Haque, Sirajul; Chandio, Javed Ahmed (International Journal of Economics, Business and Management Studies, 2013)
The public administration plays a vital role in running the affairs of governmental activities at the all levels of government. The efficiency of public personnel in respect of performance depends on the ways the public personnel are managed to be responsive in performing the respective jobs. The flight of human capital from the country not only affects the human resource development of the country but as well as overall development of the country. The brain drain is one of the critical issues faced by the public organization in Pakistan. The proposed strategic approach has been developed on the basis of Harvard HRM Model. Hence study focuses on issues of Human capital flight. The research study has tried to explore the causes of the brain drain situation and finally it has proposed strategic approach to overcome the brain drain situation in the Pakistan.